The Legend of Chao Pho Ongkharak Shrine: Dynamics, Existence, and Influencing on the Community - Kamonsujja, Wichetchay; Chomdee, Chayanon (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2022)
This academic article aims to 1) study the background of the legend of Chao Pho Ongkharak Shrine, Nakhon Nayok Province, 2) study the change in the legend of Chao Pho Ongkharak Shrine in terms of time and space, 3) study the existence of the legend and Chao Pho Ongkharak Shrine in the community, and 4) study the function of Chao Pho Ongkharak Shrine mythology influencing the community. The results revealed Chao Pho Ongkharak is The Royal Guard of King Chulalongkorn, who died while on his way to Prachin Province. that there were two legends of Chao Pho Ongkharak Shrine included the first legend mentioned he passed away of jungle fever, and the second tale stated the death because of protecting King Rama V Pavilion from the wild elephant resulted in the legend of Chao Pho Ongkharak Shrine construction and appearing the duality of the crocodile with the shrine to reinforce the sacred shrine. It discovered that the factors of "duration" and "people in the region" affect the existence and dynamic of the legend. The previous shrine was "covered" by Chinese culture. For instance, the former shrine was changed to a Chinese Shrine basis, and Chao Pho Ongkharak Icon was modified into "Bun Tao Gong" due to the significant role of the people of Chinese Descent who renovated the shrine and the existence of the "annual festival" "Provincial tourist attractions" and "Charity organizations." Moreover, the legend of Chao Pho Ongkharak Shrine influenced the community, strengthening morality and ideology, community history knowledge, and stratagems included strengthened community. Especially the identity construction of "Ongkharak" (defender) through the name of the village, district, institute songs, and school symbol to strengthen the community and maintain harmony and peace.